Early ultrasound-guided drainage of tubo-ovarian abscesses versus conservative treatment: a retrospective cross-sectional study - Antonello, Vicente S; Ramos, Suelyn Cristina P; Jimenez, Mirela F; Bassols, Felipe F (The Journal of Infection in Developing Countries, 2024)
Objective: To compare the short and long-term benefits (the length of hospital stay, surgical complications, and early clinical improvement) of adding early ultrasound-guided drainage to broad-spectrum antibiotic treatment. Methodology: Patients undergoing tubo-ovarian abscess treatment between January 2017 and June 2022 in a tertiary hospital were retrospectively evaluated. Of the patients studied, 50 subjects were treated with antibiotics alone and 63 underwent guided drainage. Twenty-one individuals underwent early drainage within 72 hours of admission, and 42 underwent guided drainage after this period. Results: There was no statistical difference in the length of hospital stay between the groups simultaneously, averaging 6.4 days for the controls, 5.1 days for the early drainage group, and 9.6 days for the late drainage group (p = 0.290). In the multiple linear regression with the length of hospital stay outcome and adjusting for potential confounding factors, there was an average reduction of 2.9 days in the hospital stay (p = 0.04) for the early drainage group (< 72 hours) compared to the controls. Early clinical improvement and an expected drop in CRP were more frequent in patients who underwent drainage. Length of hospital stay increases with abscess diameter: 0.4 [(95% CI 0.1 – 0.7) (p = 0.05)] days per centimeter, regardless of other variables. Conclusions: Ultrasound-guided drainage of tubo-ovarian abscesses associated with antibiotic therapy is an effective treatment, with few complications, and may lead to clinical improvement especially when performed early.